Benchmarking sustainable development: A synthetic meta-index approach - Laurens Cherchye; Timo Kuosmanen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
The need for monitoring countries' overall performance in sustainable development (SD) is widely recognized, but the methods for aggregating vast amounts of empirical data remain rather crude. This paper examines the so-called `benefit of doubt' weighting method as a tool for identifying benchmarks without imposing strong normative judgement about SD priorities. The weighting method involves linear optimization techniques, and allows countries to emphasize and prioritize those SD aspects for which they perform relatively well. Using this method, we construct a meta-index of SD (MISD), which combines 14 existing aggregate SD indices (developed by well-established organizations and/or expert teams) into a single synthesizing overall SD index. Within a sample of 154 countries, our index identifies six benchmark countries (three high-income countries and three uppermiddle- income countries), but also a number of seriously under-performing countries. We view this approach as a first step towards more systematic international comparisons, aimed at facilitating diffusion of the best practices and policies from the benchmark countries to the less developed world.
Keywords: Q01; O57; C43; C61; 330; sustainable development; integrated assessment; benchmarking; benefit of doubt weighting; data envelopment analysis; Nachhaltige Entwicklung; Benchmarking